Influence of digital finance accessibility on financial inclusion and bank stability: Evidence from the ASEAN - Esparas, Jameson (Animo Repository, 2022)
Over the past decade, there has been a stream of instabilities brought about by financial institutions primarily from banks. Examples of these include the Global Financial Crisis of 2008, the Sovereign Debt Crisis of 2010, and the COVID-19 pandemic of 2020. This decade also saw the rise of digital finance across the globe which encouraged greater financial inclusion across different populations. However, there has been no clear evidence on the role of digital finance in explaining bank stability when mediated by financial inclusion within an ASEAN context. As such, this study hopes to clarify the relationship between these three variables. This study gathered data for specific variables from the Global Financial Development Database of the World Bank. After which, a series of panel data regression model specification and diagnostic tests were performed. Applying the special agent theory of financial inclusion, the results justified the significant effects of all dimensions of access to digital finance on financial inclusion. Further research justified that access to digital finance by the less economically privileged populations provided the boost for this outcome. As for the effect of access to digital finance on bank stability, the resource appropriations theory applies. Finally, the mediating effect of financial inclusion was found significant in the effect of access to digital finance and bank stability through reducing unemployment. This finding is consistent with that of the systemic theory of financial inclusion. Recommendations for policymakers, future researchers, and the financial sector are provided. Keywords: digital finance, financial inclusion, bank stability, ASEAN